Developing speaking skill in EFL English course - Citra Priski Abadi (Journal on English as a Foreign Language, 2015)
The main objectives of this study are to describe factors contributing the development of speaking skill, and to describe techniques and strategies used by the teachers to develop speaking skill in EFL English Course (PEACE English Academy and PEACE Camp 4 Boy in Pare, Kediri, East Java). The research design used was an ethnography principle. The subjects of the study were 80 students of PEACE English Academy from 4 class levels, PEACE Camp 4 boy, 4 teachers and 1 home principle. The data were gained from observations, interview, and artifact and field notes. The findings depicted that (1) teachers as the main factor of presage variable were observed using many kinds of strategies, and techniques for developing speaking skills, and (2) appropriate speaking techniques and strategies were used to develop speaking skill in the mentioned different speaking class levels. The strategies and techniques are realized because teachers as the main factor applied some unique ways–how to make the English language classroom to be a lot of fun and dynamic place, to enhance students’ motivation, and to build English atmosphere in class and outside class as well.